A phase I, open-label, multicentre, first-in-human study to evaluate safety, pharmacokinetics and efficacy of AMG 404, a PD-1 inhibitor, in patients with advanced solid tumours - Yasutoshi Kuboki; Hendrik-Tobias Arkenau; Vivek Subbiah; Timothy Price; Gerald Falchook; Hans Prenen; Rafal Dziadziuszko; Hansen Wong; Iwona Lugowska; Daniel Tan; Weibing Shi; Ryota Shibaki; et al. (BMJ Open)
Objective To evaluate the safety, tolerability, pharmacokinetics (PK) and preliminary antitumour activity of AMG 404, a fully human IgG1 monoclonal antibody targeting programmed cell death-1, in patients with advanced solid tumours.Design First-in-human phase I study comprising eight dose expansion cohorts, including cohorts with microsatellite instability-high (MSI-H) tumours and non-small cell lung cancer with high programmed death-ligand 1 expression (NSCLC/PDL1-H, tumour proportion score ≥50%).Setting Conducted across 28 global sites.Participants This study enrolled adult patients with histologically or cytologically confirmed metastatic or locally advanced solid tumours not amenable to curative treatment with surgery or radiation. The inclusion criteria included a life expectancy of >3 months, ≥1 measurable or evaluable lesion per modified Response Evaluation Criteria in Solid Tumours (RECIST) V.1.1, an Eastern Cooperative Oncology Group performance status of ≤2 and adequate haematological, renal and hepatic function. Patients with prior treatment with checkpoint inhibitors, primary brain tumour or untreated or symptomatic brain metastases and leptomeningeal disease and history of other malignancy within the past 2 years were excluded.Interventions The planned doses were 240 mg, 480 mg and 1050 mg of AMG 404 administered every 4 weeks (Q4W).Primary and secondary outcome measures Primary endpoints were dose-limiting toxicities (DLTs), treatment-emergent adverse events, treatment-related adverse events, changes in vital signs and clinical laboratory tests. Secondary endpoints included PK parameters, incidence of antidrug (AMG 404) antibodies and antitumour activity assessed per modified RECIST V.1.1 (objective response, duration of response, progression-free survival (PFS), disease control and duration of stable disease).Results A total of 171 patients were enrolled; 168 were treated. Median (range) follow-up was 36.3 weeks (1.6–137.1). No DLTs were observed. Grade 3 and serious treatment-related adverse events occurred in 16 (9.5%) and 12 (7.1%) patients, respectively. The 480 mg Q4W dose was selected as the recommended phase II dose. AMG 404 serum exposure increased approximately dose proportionally. The objective response rate (80% CI) was 19.6% (15.7–24.1) for the overall population and 36.6% (26.4–47.8) and 30.8% (14.2–‍52.3) for cohorts with MSI-H tumours (n=41) and NSCLC/PDL1-H (n=13), respectively. The overall disease control rate (80% CI) was 54.8% (49.5–59.9). The median (80% CI) PFS was 3.7 (3.5–4.5) months for the overall population and 14.8 (9.0–not estimable) and 4.4 (2.2–9.7) months for cohorts with MSI-H tumours and NSCLC/PDL1-H, respectively.Conclusions AMG 404 monotherapy was tolerable at the tested doses, with encouraging antitumour activity observed across tumour types.Trial registration number NCT03853109.